E-Mengaji System for Yayasan Restu - ABD AZIZ, YUMNI; Hairulnizam Mahdin, (Applied Information Technology And Computer Science, 2024)
The E-Mengaji system, developed to facilitate online Quranic learning by Yayasan Restu, serves as a comprehensive management tool for classes, students, and teachers. Currently relying on manual record-keeping, the system faces challenges such as inefficiencies, data loss risks, and scalability issues. The goal is to improve the operations' effectiveness and productivity while easing current difficulties. With a focus on educational technology and information management, the system comprises modules for user and class management, payment processing, and analytics. The system employs Laravel, an advanced technology, to address problems with traditional methods and uses a methodical approach with Agile design phases and rigorous testing to ensure a reliable and error-free system. E-Mengaji accommodates the unique needs of various organizations through scalability and customization, promoting improved operational agility and organizational performance. Overall, E-Mengaji system has been successfully developed with a login module, manage user module, manage profile module, course registration module, calendar module, manage class module, manage feedback module and attendance module